2008
DOI: 10.1016/j.neuron.2008.07.003
|View full text |Cite
|
Sign up to set email alerts
|

A Presynaptic Gain Control Mechanism Fine-Tunes Olfactory Behavior

Abstract: Early sensory processing can play a critical role in sensing environmental cues. We have investigated the physiological and behavioral function of gain control at the first synapse of olfactory processing in Drosophila. We report that olfactory receptor neurons (ORNs) express the GABAB receptor (GABABR) and its expression expands the dynamic range of ORN synaptic transmission that is preserved in projection neuron responses. Strikingly, we find that different ORN channels have unique baseline levels of GABABR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
403
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 314 publications
(430 citation statements)
references
References 49 publications
(69 reference statements)
24
403
3
Order By: Relevance
“…Recent studies of peripheral olfactory signal processing in Drosophila have shown that there are afferent and local excitatory cholinergic circuits, combined with presynaptic and postsynaptic GABAergic inhibition of ORNs and interneurons (8,9,13,14,28). We now demonstrate a second presynaptic inhibitory pathway mediated by DTK-expressing LNs, providing an additional modulation mechanism in peripheral olfactory processing.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Recent studies of peripheral olfactory signal processing in Drosophila have shown that there are afferent and local excitatory cholinergic circuits, combined with presynaptic and postsynaptic GABAergic inhibition of ORNs and interneurons (8,9,13,14,28). We now demonstrate a second presynaptic inhibitory pathway mediated by DTK-expressing LNs, providing an additional modulation mechanism in peripheral olfactory processing.…”
Section: Discussionsupporting
confidence: 53%
“…Presynaptic GABAergic inhibition of the ORNs has been shown in both Drosophila (8,9) and in mammals (10)(11)(12). Conversely, cholinergic LNs in the Drosophila antennal lobe have been suggested to increase and redistribute odor-evoked activity at low odor concentrations (13,14).…”
mentioning
confidence: 99%
“…Signal transduction has been implicated in the regulation of behavior across disparate taxa (21), and several genes on the All Eusocial gene list in this category have known roles in behavior and neuronal function, including metabotropic GABA-B receptor subtype 1 (22). Our results provide further evidence that signal transduction may be a general target of selection during behavioral evolution.…”
Section: Discussionmentioning
confidence: 52%
“…The activity of ORNs, either excitation or inhibition, provides behaviorally relevant information about odorants such as their identity, concentration, and source. The information transduced by an ORN is processed in the antennal lobe (12,13) and sent via PNs to the mushroom bodies, which are believed to be centers for olfactory learning and memory (14,15).…”
mentioning
confidence: 99%